Effect of p27mt gene on apoptosis of the colorectal cancer cell line Lovo - Chen, Jun (The WJG Press and Baishideng, 2009)
AIM: To construct p27mt recombinant adenovirus, transfect the colorectal cell line Lovo and observe the effects of p27mt on Lovo cell apoptosis and cell cycle inhibition. METHODS: We constructed recombinant adenovirus containing p27mt by homologous recombination in bacteria. The colorectal cancer cell line Lovo was infected with recombinant replication-defective adenovirus Ad-p27mt, and expression of p27mt was determined by Western blotting; the inhibitory effect of p27mt on Lovo cells was detected by cytometry. Cell cycle was determined by flow cytometry. DNA fragment analysis identified the occurrence of apoptosis. RESULTS: The recombinant adenovirus which already contained p27mt target gene was successfully constructed. When multiplicity of infection was ≥ 50, the infection efficiency was 100%. After transfection of Lovo cells with Ad-p27mt the cells had high p27 expression which was identified by immunoblotting assay. PI staining and flow cytometry showed that 77.96% of colorectal cancer cells were inhibited in phase G(0)/G(1), while in the Ad-LacZ group and blank control group, 27.57% and 25.29% cells were inhibited in the same phase, respectively. DNA fragment analysis, flow cytometry and TUNEL assay demonstrated that p27mt is able to induce apoptosis in colorectal cancer cells. CONCLUSION: p27mt has an obvious blocking effect on colorectal cancer cell cycle, and most cells were inhibited in phase G(0)/G(1). Therefore, p27mt can induce apoptosis in colorectal cells.